Logosfera a etyka społeczeństwa komunikacji - Lepa, bp Adam (Annales. Etyka w Życiu Gospodarczym, 2008)
This paper is concerned with the attitude of communication society towards the layer of ethical values. Contrary to what constitutes information society, the conception of communication society is based on the credibility of information, which is a significant component of human communication, and social bonds, which are the basis for any communication. Therefore, it is hypothesized that logosphere, which is the environment of the word, can effectively influence the ethical foundations of communication society and contribute to the development of such society. The chief asset of logosphere is based on its properties: the primacy of the word, dialogicity, and its environmental character. Owing to these features logosphere can positively affect the ethical layer of communication society, provided it constitutes an arranged environment of the word.